2017
DOI: 10.1159/000455705
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Hearing Dysfunction: Facts and Outlook

Abstract: In medicine, biomarkers are a metric for disease state. More generally, a biomarker is anything that can be used as an indicator for a particular disease state or any physiological state of an organism. Here, we introduce functional and molecular biomarkers that are useful for categorizing defined subtypes of hearing disorder, which can help to selectively trace a particular dysfunction of the inner ear and the auditory pathway to disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 153 publications
(189 reference statements)
0
41
0
Order By: Relevance
“…OHC electromotility forms the basis of the sound-evoked neural potentials at threshold (Marcon and Patuzzi, 2008). To assess OHC function, we recorded ear canal sound pressure changes induced by distortion products of the otoacoustic emissions (DPOAEs) (Shera and Guinan, 1999) that are specifically generated upon intact electromechanical responses of OHCs (El-Badry and McFadden, 2007;Rüttiger et al, 2017). We analyzed the frequency-specific thresholds of DPOAE signals from amplitude input-output functions by presenting pure-tone sounds from f2 5 4-32 kHz and increasing sound level (L1 5 210-65 dB SPL) in NO-GC isoform-specific KO mice compared with age-matched WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…OHC electromotility forms the basis of the sound-evoked neural potentials at threshold (Marcon and Patuzzi, 2008). To assess OHC function, we recorded ear canal sound pressure changes induced by distortion products of the otoacoustic emissions (DPOAEs) (Shera and Guinan, 1999) that are specifically generated upon intact electromechanical responses of OHCs (El-Badry and McFadden, 2007;Rüttiger et al, 2017). We analyzed the frequency-specific thresholds of DPOAE signals from amplitude input-output functions by presenting pure-tone sounds from f2 5 4-32 kHz and increasing sound level (L1 5 210-65 dB SPL) in NO-GC isoform-specific KO mice compared with age-matched WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The auditory stimulus-evoked ABR wave I (Fig. 3) reflects the summed activity of the auditory nerve fibers (Melcher and Kiang, 1996) and is a useful functional biomarker for auditory nerve degeneration after noise exposure (Rüttiger et al, 2017).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we observed that the variation of stress hormone levels in mature female rats correlated with a prominent variation in auditory nerve function for processing especially high‐frequency stimuli. These variations in responsiveness to sound occur independently of OHC function as assessed from DPOAEs (43) that define hearing thresholds via OHC electromotile response properties (23, 44, 45). We also did not observe any significant influence from pretreatment with the GC antagonist, mifepristone, or the mineralocorticoid antagonist, spironolactone, on hearing threshold 2–3 wk after nontraumatic (sham) or traumatic sound exposure (AT).…”
Section: Discussionmentioning
confidence: 99%
“…DPOAEs induce IE-canal sound pressure changes (Shera & Guinan, 1999) that are specifically generated upon intact electromechanical responses of OHCs (El-Badry & McFadden, 2007;Rüttiger, Zimmermann, & Knipper, 2017). We analyzed the thresholds of DPOAE I/O functions of emission amplitudes evoked by f 2 = 4 to 32 kHz pure-tone sounds in GDNF mutant mice in comparison to age-matched control mice.…”
Section: Hearing Thresholds and Ohc Function Of Atoh1-cre-and Trkc-mentioning
confidence: 99%